Pengaruh Harga Karpet, Pendapatan Konsumen Dan Usia terhadap Permintaan Karpet di Pasar Sudimampir Kota Banjarmasin - Muhammad Rifani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research was conducted to know (1) what is the price of the carpet, consumer income, and age take effect simultaneously to a request of the carpet Market inSudimampir town of Banjarmasin; (2) were the most dominant Factor effect partially to a right of the carpet Market in Sudimampir town of Banjarmasin. Respondents who were sampled in the processing of the data amounted to 41 people. Data processed by using multiple linear analyses to see the influence of the independent variable (the price of the carpet, consumer income, and age) of the dependent variable (the demand for carpet).Multiple linear regression results in this research prove a significant relationship between the price of carpets and carpet requests against consumer income in the marketSudimampir, the city of Banjarmasin. This relationship indicates that the higher the cost of the rug then requests, the carpet will go down; otherwise, when the price is low, then the carpet demand is going up. In addition, the greater the income consumers then request, the carpet will be increased; on the contrary, when consumer income is small, then the carpet request will be declined as for the age to do not significantly to request the carpet on the market Sudimampir the city of Banjarmasin.